Legislar en la América hispánica en la temprana edad moderna Procesos y características de la producción de los Decretos del Tercer Concilio Provincial Mexicano (1585) - Moutin, Osvaldo Rodolfo (Global Perspectives on Legal History, 2016)
"The Third Mexican Provincial Council, celebrated in 1585, has always been considered a cornerstone of the canonical law of Spanish America, both with regard to its content and the long period and vast territory in which it was in force. New possibilities of research had been made possible due to the publication of the working manuscripts in recent years, enabling a better understanding of the juridical work produced by the bishops. Given these new materials, the author has delved deeper into the drafting processes carried out by the provincial council. Taking a close look at the reports sent to the council, the theological and juridical treaties, and other conciliar and synodal legislation, along with the consultations to jurists and theologians, the author has identified different processes of drafting of the conciliar decrees. The result of this research allows us to relocate the authorship of the conciliar decrees to the Mexican episcopate as well as establish the degree of their originality. Locality of the law and its significance in the legal order in force at that time is one of the characteristics of the body of decrees promulgated at the Third Mexican Provincial Council."